Explaining the Experiences of Social Workers in Utilizing Professional Capital to Deal with Client Violence - Nasrin Babaeian; Ghoncheh Raheb; Fariba Borhani; Atieh Hashieh-Baf (Kerman University of Medical Sciences, 2021)
Introduction: Establishing an appropriate and effective professional relationship in social work practices is always emphasized, but sometimes this relationship is likely to be exposed to violence. The purpose of this study was to explain the experiences of social workers in utilizing professional capital to deal with clients' violence.Methods: The present study was conducted using a conventional qualitative content analysis approach through 20 semi-structured interviews with 17 social workers selected via purposive sampling. The interviews continued until the data saturation and the identification of related themes and categories.Results: Based on the findings from the data analysis, four main themes (knowledge, experiences, techniques, and commitment to professional principles and values) and 14 subthemes related to the professional capital were identified.Conclusion: The results of this study showed that the social workers try to cope with the violence of clients by utilizing knowledge, experiences, professional techniques and their commitment to professional principles and values in such a way to cause the least possible harm to the clients and themselves. Promoting the education and learning of violence coping skills, especially during internship courses, is one of the issues that need to be addressed from a social, organizational, and academic perspective.